The Unique Role of Early Spelling in the Prediction of Later Literacy Performance. (3rd September 2019) - Treiman, Rebecca; Hulslander, Jacqueline; Olson, Richard K.; Willcutt, Erik G.; Byrne, Brian; Kessler, Brett
ABSTRACT: We examined the predictive value of early spelling for later reading performance by analyzing data from 970 U.S. children whose spelling was assessed in the summer following the completion of kindergarten ( M age = 6 years; 3 months). The word reading performance of most of the children was then tested after the completion of Grade 1 (age 7;5), Grade 2 (8;5), Grade 4 (10;5), and Grade 9 (15;5). A computer-scored measure of postkindergarten spelling was a significant predictor of later reading performance even after taking into account postkindergarten phonological awareness, reading, and letter-sound knowledge and prekindergarten vocabulary. The results suggest that, by the end of kindergarten, spelling is more than just a proxy for phonological awareness and letter-sound knowledge. Given the information that spelling provides, it should be considered for inclusion when screening children for future literacy problems.